Analisis Performa Jaringan 5G dengan Metode MIMO - Satriawan, Hamdani (Journal of Computer Science and Information Technology, 2025)
This study aims to analyze the performance of 5G networks with the implementation of Multiple Input Multiple Output (MIMO) technology through a simulation approach using NS-3 software. Evaluations were conducted on three antenna configurations, namely SISO (1x1), MIMO 2x2, and MIMO 4x4, in two environmental scenarios: urban and rural. The parameters analyzed include throughput, latency, and signal-to-noise ratio (SNR). The simulation results show that the MIMO 4x4 configuration provides the most significant performance improvement compared to SISO, with an average throughput increase of up to 40%, a latency reduction of 25%, and an SNR increase of up to 10 dB. In addition, MIMO is proven to be able to maintain stable performance in dense traffic conditions and high interference, especially in urban environments. Better channel efficiency is also achieved through the utilization of spatial multiplexing and beamforming. These results strengthen the evidence that MIMO is a key technology in the development of 5G networks, especially in addressing the needs of high-speed communications and real-time services. This study concludes that MIMO technology has great potential to be widely implemented in 5G networks in Indonesia, and is an important foundation for the implementation of future communication systems that are smarter, faster, and more reliable.